Management of oral anticoagulation after intracerebral hemorrhage - Kuramatsu, Joji; Huttner, Hagen (International Journal of Stroke, 2019)
Background The most recent years have significantly expanded knowledge regarding risks and benefits of resuming oral anticoagulation (OAC) after intracerebral hemorrhage (ICH). No randomized data is yet available, though several large observational studies and meta-analyses have investigated the impact of resuming OAC on thromboembolic versus hemorrhagic complications in these high-risk patients after ICH. Aims The present review will summarize the most important studies conducted over the last years and will focus on relevant factors help guiding on decision-making on whether to start OAC after ICH. Summary of review Several important factors (demographic, co-morbidities, clinical characteristics) need to be considered before individual decision-making for or against OAC is employed. Existing observational data suggest that patients after ICH with indication for long-term oral anticoagulation benefit from OAC given significant reductions of thromboembolic events without significantly increasing bleeding complications. Studies even suggest that thereby also clinical outcomes may be improved. Prospective trials currently recruiting patients will clarify whether OAC after ICH - or left atrial appendage closure as a meaningful alternative - is of clinical net-benefit. Conclusions Large sized and well-executed investigations (moderate quality of evidence) are showing that OAC resumption after ICH decreases thromboembolic complications and long-term mortality without significantly increasing bleeding complications. Further, data suggest that resumption may be safer in non-lobar ICH compared to lobar ICH, but overall, thoughtful selection, strict blood pressure control, and precise communication are paramount before starting a patient on OAC after ICH.
CRIS-Team WoS Importer:2019-04-02